Analisis Perhitungan Biaya Produksi Dengan Metode Variable Costing Pada PT. Gudang Garam Tbk. Padang Sidempuan - Nadila, Riska; Kamila, Kamila; Nasution, Muhammad Lathief Ilhamy (Jurnal Informatika, 2024)
Variable costing method is a method of determining the cost of production that classifies costs based on cost behavior. The calculation of the cost of production is an important thing to note because of the increasing competition between companies in producing quality products at quite competitive prices. The purpose of this study was to analyze the calculation of the cost of production using the variable costing method for the selling price of Cigarette Clove Filters at PT. Gudang Garam. Based on the calculation of the cost of production using the company method, it is higher than the calculation using the variable costing method. The cost of production using the company method is IDR 100,704,757,320 and the calculation of the cost of production using the variable costing method is IDR 68,304,757,320. Determining the selling price of the method calculatiion of the cost of production using the company method is higher than the variable costing method of IDR 1,510.57/stick. While the calculation of the cost of production using the variable costing method, the unit selling price of the product is IDR 1,024.57/stick. The difference in the selling price of this product unit occurs because the calculation of the cost of production is also different.